2012
DOI: 10.1080/13607863.2012.684664
|View full text |Cite
|
Sign up to set email alerts
|

Health status and well‐being of older adults living in the community and in residential care settings: Are differences influenced by age?

Abstract: The objective is to identify the differences and the main factors influencing health status and well-being variables between institutionalized and non-institutionalized older adults, as well as the interaction effect of institutionalization and age. Data on a total of 468 older adults from a national survey on non-institutionalized and from a study on institutionalized older people were analyzed. Socio-demographic variables and measures on well-being (Personal Well-being Index, PWI), health status (EQ-5D), fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 37 publications
5
46
0
3
Order By: Relevance
“…A study among US nursing homes found the prevalence of dementia among newly admitted residents to be 48.2 % (Magaziner et al, 2000); a Norwegian study found that about 80 % of residents showed some dementia-type symptoms (Nygaard, Naik, & Ruths, 2000). In addition, comparing residents and community dwellers without cognitive impairment, residents have significantly worse scores on functional ability, depression, satisfaction with life, and loneliness (Rodriguez-Blazquez et al, 2012). Regarding health-related quality of life, cognitively non-impaired residents have significantly worse scores on all dimensions compared to the community dwelling, except for social functioning, with the largest difference regarding physical functioning .…”
Section: Residential Aged Carementioning
confidence: 91%
“…A study among US nursing homes found the prevalence of dementia among newly admitted residents to be 48.2 % (Magaziner et al, 2000); a Norwegian study found that about 80 % of residents showed some dementia-type symptoms (Nygaard, Naik, & Ruths, 2000). In addition, comparing residents and community dwellers without cognitive impairment, residents have significantly worse scores on functional ability, depression, satisfaction with life, and loneliness (Rodriguez-Blazquez et al, 2012). Regarding health-related quality of life, cognitively non-impaired residents have significantly worse scores on all dimensions compared to the community dwelling, except for social functioning, with the largest difference regarding physical functioning .…”
Section: Residential Aged Carementioning
confidence: 91%
“…Geriatric or late life depression is one of the significant mental health issues for older people (Bolger, 2005) because it may link to health status and well-being of older people (Rodriguez-Blazquez et al, 2012). This is particularly true of older people living in homes for the aged which provided care at the minimum requirement by public or government sector for the poor, those who have been neglected or abused, or who have no family caregivers to look after them.…”
Section: Factors Related To Depression Among Older People Living In Hmentioning
confidence: 99%
“…Socialinės globos paslaugos vyresnio amžiaus asmenims yra šiuolaikinės socialinių paslaugų sistemos sudedamoji dalis, kuri visuotinio Europos gyventojų senėjimo kontekste tampa vis aktualesnė (Spirgienė ir Macijauskienė, 2008;Vaškevičiūtė ir Naujanienė, 2011;Rodriguez-Blazquez ir kt., 2012). Nors senėjimas namuose įprastai laikomas tinkamiausia vieta vyresnio amžiaus asmenų globai, vis daugiau šių asmenų tenka susidurti su persikėlimo į globos įstaigą iššūkiu (Rodriguez-Blazquez ir kt., 2012; Rijnaard ir kt., 2016).…”
Section: Tapimas Socialiai Globojamu Asmeniu Kaip Iššūkis Tapatumui Vunclassified